TINJAUAN YURIDIS PENEGAKAN HUKUM TERHADAP INFLUENCER DALAM MEMASARKAN PLATFORM INVESTASI - Wiyaka, Jessica; Hendri Jayadi; Tomson Situmeang (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
One of the investments that is currently in great demand in public is online investment trading. Trading is a form of business, in the form of buying and selling, both stocks, currencies, gold, etc. Traders take advantage of trends and changes in momentum in stocks that fluctuate greatly in price to make profits. In order to attract public interest, one of the most common forms of promotion is to involve influencers as to promote the investment. The purpose of the study is to find out legally about the laws in force in Indonesia regarding influencers in promoting the online investment platforms and to analyze legally the legal actions taken against influencers in promoting the illegal online investment platforms. The research method is normative law with the nature of descriptive research. Data sources consist of secondary data and Legislation, legal cases, scientific papers and articles, and qualitative analysis techniques.The forms of investment fraud that occur among the public at this time are divided into three, online investment, fake cooperatives, and fake Arisan, but the most frequent victim is online investment which offers very high profits.In promoting illegal investments In general, influencers offer fraudulent investments by means of lures and even with coercion so that potential investors want to invest the investment. Influencers use online media as a means for actors to find targets so that they are interested in making fake investments. This study concluded that promotion itself is regulated in the consumer protection law, and the role of influencers is also regulated in the capital market law. Then facilities and advertisements through electronic media are regulated in the Electronic Information and Transaction Law. The influencer’s criminal liability for investment fraud in the criminal act of trading investment fraud only includes imprisonment and fines. Meanwhile, the aspect of compensation for victims of fraud relates to the scope of civil law with the merger of claims for compensation in criminal cases with the assistance of protection from the Witness and Victim Protection Institute and the Financial Services Authority